eROSITA detection of flares from the Be/X-ray binary A0538-66 - Ducci, L.; Mereghetti, S.; Santangelo, A.; Ji, L.; Carpano, S.; Covino, S.; Doroshenko; Haberl, F.; Maitra, C.; Kreykenbohm, Ingo; Udalski, A. (Astronomy & Astrophysics, 2022)
In 2018, XMM-Newton observed the awakening in X-rays of the Be/X-ray binary (Be/XRB) A0538-66. It showed bright and fast flares close to periastron with properties that had never been observed in other Be/XRBs before. We report the results from the observations of A0538-66 collected during the first all-sky survey of eROSITA, an X-ray telescope (0.2-10 keV) on board the Spektrum-RoentgenGamma satellite. eROSITA caught two flares within one orbital cycle at orbital phases phi = 0.29 and phi = 0.93 (where phi = 0 corresponds to periastron), with peak luminosities of similar to 2-4 x 10(36) erg s(-1) (0.2-10 keV) and durations of 42 <= Delta t(fl) <= 5.7 x 10(4) s. The flare observed at phi approximate to 0.29 shows that the neutron star can accrete considerably far from periastron, although it is expected to be outside of the circumstellar disk, thus providing important new information about the plasma environment surrounding the binary system. We also report the results from the photometric monitoring of A0538-66 carried out with the REM, OGLE, and MACHO telescopes from January 1993 until March 2020. We found that the two sharp peaks that characterize the orbital modulation in the optical occur asymmetrically in the orbit, relative to the position of the donor star.
CRIS-Team WoS Importer:2022-06-17
Keywords: accretion; accretion disks; stars: neutron; X-rays: binaries; X-rays: individuals: 1A 0538-66